Perancangan Ulang Rem Tromol Sepeda Motor Supra Menggunakan Metode Reverse Engineering dengan Analisis Von Mises - Wistikhirana, Hanandira; Alfiansyah, Achmad Adfa; Luqyana, Dhiya (JTRM (Jurnal Teknologi dan Rekayasa Manufaktur), 2026)
This study presents a redesign of the drum brake system on a Honda Supra motorcycle using a reverse engineering approach. Innovation was carried out by utilizing aluminum alloy as the brake shoe material to reduce weight and enhance corrosion resistance. In addition, a Non-Asbestos Organic (NAO) brake lining was applied, known for its high friction performance and excellent wear resistance. Design modifications include increasing the rib thickness of the brake shoe to reduce stress concentration and adding a chamfered surface to the brake lining, with a thickness of 5 mm. Structural strength was evaluated through Finite Element Analysis (FEA), using von Mises stress as the performance indicator. The results indicate that the redesigned structure and material successfully reduce stress concentration.